The Illusion of Certainty: Medical Realism and Its Uncritical Reception in Islamic Thought - Amana Raquib; Marium Ezam Qazi (Universitas Islam Internasional Indonesia, 2026)
This study explores the nature and methods of biomedical reasoning to ascertain its epistemic standing. The analysis of the metaphysical presuppositions that undergird contemporary biomedicine as well as its logical weaknesses is needed, since biomedicine, when appropriated from within the Islamic tradition of theology and jurisprudence, is assumed to have extremely high epistemic worth and prestige due to its practical efficacy and success. When biomedicine interacts with the Islamic knowledge tradition (theology and jurisprudence), these unquestioned assumptions lead to the subsuming of the Islamic worldview by the biomedical worldview, in which Muslims tend to interpret their doctrines and principles under the undeclared philosophical position of scientific realism (SR). The method employed in this paper is to reveal the underlying metaphysics of modern biomedicine and the lack of finality (qaṭʿiyya) in its reductionist working principles. Through this method, this paper argues that the high level of ẓann (both in terms of conjecture and doubt) that characterizes the knowledge (theoretical models) and practice of biomedicine does not warrant its use within the sphere of Islamic theology. By delineating the inherent metaphysical reduction and various logical weaknesses in biomedicine, this paper tends to open the discourse in which Muslim scholars should treat biomedical knowledge as instrumental knowledge for pragmatic ends, instead of adopting it in a scientific realist fashion, providing a provisional outline of such a framework.